2023
DOI: 10.1186/s12864-023-09539-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequential viral introductions and spread of BA.1 across Pakistan provinces during the Omicron wave

Abstract: Background COVID-19 waves caused by specific SARS-CoV-2 variants have occurred globally at different times. We focused on Omicron variants to understand the genomic diversity and phylogenetic relatedness of SARS-CoV-2 strains in various regions of Pakistan. Methods We studied 276,525 COVID-19 cases and 1,031 genomes sequenced from December 2021 to August 2022. Sequences were analyzed and visualized using phylogenetic trees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The second period, B (10th December 2020–9th December 2021) covered the pandemic waves in 2021 associated with Alpha, Beta, Gamma and Delta variants in Pakistan 26 , 27 . The third period, C (10th December 2021–15th August 2022) associated with the Omicron wave in 2022 17 . Mortality due to COVID-19 increased at the beginning of the pandemic in 2020 (A) and then during 2021 (B), peaking in July.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second period, B (10th December 2020–9th December 2021) covered the pandemic waves in 2021 associated with Alpha, Beta, Gamma and Delta variants in Pakistan 26 , 27 . The third period, C (10th December 2021–15th August 2022) associated with the Omicron wave in 2022 17 . Mortality due to COVID-19 increased at the beginning of the pandemic in 2020 (A) and then during 2021 (B), peaking in July.…”
Section: Resultsmentioning
confidence: 99%
“…The Omicron BA.2 lineage subvariant XBB, first identified in India in August 2022, became the most dominant by the end of 2022 15 , 16 . Phylogenetic analysis of Omicron variants in provinces across Pakistan revealed that BA.1 and BA.2 variants were first introduced in the province of Sindh 17 .…”
mentioning
confidence: 99%